Controlling Photoconductivity in PBI Films by Supramolecular Assembly - Draper, Emily R. (Chemistry, 2018)
Perylene bisimides (PBIs) self‐assemble in solution. The solubility of the PBIs is commonly changed through the choice of substituents at the imide positions. It is generally assumed this substitution does not affect the electronic properties of the PBI, and that the properties of the self‐assembled aggregate are essentially that of the isolated molecule. However, substituents do affect the self‐assembly, resulting in potentially different packing in the formed aggregates. Here, we show that the photoconductivity of films formed from a library of substituted PBIs varies strongly with the substituent and demonstrate that this is due to the different ways in which they pack. Our results open the possibility for tuning the optoelectronic properties of self‐assembled PBIs by controlling the aggregate structure through careful choice of substituent, as demonstrated by us here optimising the photoconductivity of PBI films in this way.